Sistem Prediksi Penjualan Pupuk Kelapa Sawit PT. Agro Subur Anugrah Menggunakan Metode Single Exponential Smoothing: Sistem Prediksi Penjualan Pupuk Kelapa Sawit PT. Agro Subur Anugrah Menggunakan Metode Single Exponential Smoothing - Sunanto, Sunanto; Mualfah, Desti; Ronaldo, Aditya (Universitas Muhammadiyah Riau, 2024)
A factory is an industrial facility where raw materials or components are processed or processed into finished products. The production process in a factory can involve a wide range of activities, including manufacturing, processing, assembly, and energy production. PT. Agro Subur Anugrah is the owner of the Ultra Agrotan organic fertilizer factory which is made from empty palm oil bunches. The Ultra Agrotan fertilizer factory started production in 2017 with a production capacity of 15 tons per day. Due to the increase in the price of chemical fertilizers, demand for Ultra Agrotan fertilizer increased, so production was increased to 50 tons per day. Fertilizer sales are greatly influenced by various factors, namely weather conditions, soil quality, soil type, age of oil palm plants, and cultivation practices carried out by farmers or plantation companies which are not fixed every year, so that fertilizer sales are not smooth due to these conditions. Large unsold fertilizer stocks will harden, this can be detrimental to the company. In this case, a system is applied that can predict the amount of fertilizer production every day, week, month and year based on fertilizer demand data in the previous year, namely fertilizer sales data for 2017, 2018, 2019, 2020, 2021 and 2022. The application is presented using a web-based The single exponential smoothing method is expected to help calculate the amount of production, stock and consumer demand for Ultra Agrotan fertilizer.